Motivation as the Predictor of Employee Performance - Burhanudin; Kuswantoro, Ferri; Mulyadi (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This study aims to examine the motivational effect of Maslow's hierarchy of needs on employee performance. The sample in this study was 67 employees of PT. Sari Husada Yogyakarta. The data collection technique used a questionnaire, while the data analysis technique used multiple linear regression. The results showed that: (1) physiological needs have a significant effect on employee performance; (2) the need for a sense of security has a significant effect on employee performance; (3) social needs have a significant effect on employee performance; (4) the need for appreciation has a significant effect on employee performance; and (5) the need for self-actualization has a significant effect on employee performance.